Academic Predictors of Early Adolescents' Perceived Popularity: The Moderating Effects of Classroom Academic Norm Salience - Zhang, Yunyun; Ren, Ping; Li, Xin; Liu, Hongyun; Luo, Fang (Frontiers in Education, 2019)
In order to extend our understanding of the effect of academic motivations and outcomes on the social status of adolescents in the classroom context, this study examined the predictive role of academic achievement and achievement goals on early adolescents’ perceived popularity and the effect of classroom academic norm salience on these relationships. 2,558 adolescents in grade 7 (mean age 12.97 years) in mainland China participated in the study. Hierarchical linear modelling (HLM) was used to examine predictive effects of within-class and between-class predictors on perceived popularity. The results showed that only girls' academic achievement and performance-approach goals of both genders positively predicted adolescents’ perceived popularity. Classroom academic norm salience strengthened the negative role of performance-avoidance goals on perceived popularity, and it seems to undermine gender differences in the effect of mastery goals on perceived popularity. The current study would not only fill the gaps in research on the relationship between academic development and social status, but also reveal the special influence and significance of collective cultures such as Chinese in this field and show a different relationship pattern from those found in previous Western studies.